Exploring Local Food-Based Supplementary Feeding for Pregnant Women with Chronic Energy Deficiency: A Qualitative Study in Indonesia - Harna Harna; Andi Muh Asrul Irawan (PT.Mantaya Idea Batara, 2026)
Background: Chronic Energy Deficiency (CED) among pregnant women continues to pose a significant public health challenge in Indonesia, increasing risks for both maternal and fetal health. This study analyzed the compliance of pregnant women at risk of CED with the Supplementary Feeding (PMT) program and explored the potential of local foods as alternative supplements. Methods: A descriptive qualitative approach was employed from October to December 2023 at the Parung Panjang Public Health Center in Bogor Regency. Data were obtained through in-depth interviews with nine informants, including five pregnant women at risk of CED, two healthcare professionals (a nutritionist and a midwife), and two community health volunteers. Thematic analysis was used, and findings were validated through source triangulation. Results: Results indicated that non-compliance with the PMT program was primarily due to distribution barriers, reporting gaps, and sensory fatigue. The findings indicate that local food-based supplementary feeding may be acceptable to pregnant women with CED and could serve as an alternative to manufactured biscuits. Cassava and catfish were identified as promising raw materials because of their abundant availability and compatibility with local dietary practices. Conclusion: Further product development and intervention studies are recommended to assess nutritional adequacy, acceptability, adherence, and effectiveness.